The ZInEP Epidemiology Survey: background, design and methods. Issue 4 (18th June 2014) - Ajdacic‐Gross, Vladeta; Müller, Mario; Rodgers, Stephanie; Warnke, Inge; Hengartner, Michael P.; Landolt, Karin; Hagenmuller, Florence; Meier, Magali; Tse, Lee‐Ting; Aleksandrowicz, Aleksandra; Passardi, Marco; Knöpfli, Daniel; et al.
Abstract This article introduces the design, sampling, field procedures and instruments used in the ZInEP Epidemiology Survey. This survey is one of six ZInEP projects (Zürcher Impulsprogramm zur nachhaltigen Entwicklung der Psychiatrie, i.e. the "Zurich Program for Sustainable Development of Mental Health Services"). It parallels the longitudinal Zurich Study with a sample comparable in age and gender, and with similar methodology, including identical instruments. Thus, it is aimed at assessing the change of prevalence rates of common mental disorders and the use of professional help and psychiatric sevices. Moreover, the current survey widens the spectrum of topics by including sociopsychiatric questionnaires on stigma, stress related biological measures such as load and cortisol levels, electroencephalographic (EEG) and near‐infrared spectroscopy (NIRS) examinations with various paradigms, and sociophysiological tests. The structure of the ZInEP Epidemiology Survey entails four subprojects: a short telephone screening using the SCL‐27 (n of nearly 10, 000), a comprehensive face‐to‐face interview based on the SPIKE (Structured Psychopathological Interview and Rating of the Social Consequences for Epidemiology: the main instrument of the Zurich Study) with a stratified sample (n = 1500), tests in the Center for Neurophysiology and Sociophysiology (n = 227), and a prospective study with up to three follow‐up interviews and further measures (n = 157). In sum, the four subprojects of the ZInEP Epidemiology Survey deliver a large interdisciplinary database. Copyright © 2014 John Wiley & Sons, Ltd.